Life in the shadows: a memoir - Dulat, A. S. (Gurugram Harper Collins, 2023)
From a Partition-bloodied childhood in Lahore and New Delhi to his early years as a young intelligence officer; from meetings with international spymasters to travels around the world; from his observations on Kashmir-political and personal-post the abrogation of Article 370, to his encounters with world leaders, politicians and celebrities; moving from Bhopal to Nepal and from Kashmir to China.
Keywords: Autobiography